Opportunity and Challenges of Sweet Orange (Citrus sinensis L. Osbeck) Production in Sindhuli and Ramechhap Districts - Acharya, Umesh Kumar; Shrestha, Hari Krishna (Nepalese Horticulture, 2021)
Household survey and focus group discussion (FGD) were carried out in year 2017/18 in Sindhuli and Ramechhap districts in order to identify scope and constraints for better sweet orange production. A semi-structured questionnaire acquiring household and orchard information, production, post-harvest operation as well as marketing situation was administered in the survey of 60 and 62 households in Sindhuli and Ramechhap, respectively. Prior to household survey, a FGD was carried out in each site of Sindhuli and Ramechhap to collect general information and cross check the individual response. Poor orchard management, lack of irrigation, infestation of a number of insects including fruit fly, infection of a number of diseases as well as lack of financial facilities were reported as key constraints to grow sweet orange industries in these districts. The yield of sweet orange was found less than national average yield in both survey sites. Various measures to increase production and to improve post-harvest quality of fruits have been suggested based on situation analysis.